Lessons Learned to Aid in Developing Fatigue Risk Management Plans for Resident Physicians. Issue 2 (15th March 2019) - Kassam, Aliya; Cowan, Michèle; Topps, Maureen
Abstract: Phenomenon : Fatigue is a significant risk factor for deterioration in performance, which may lead to medical errors and reduced well-being in resident physicians (residents). Sleep deprivation, which has been studied extensively, is only one contributor to fatigue. Given the complexity of fatigue and its relationship with resident performance, the National Steering Committee on Resident Duty Hours in Canada recommends that all residency education programs develop a fatigue risk management plan (FRMP) for their residents. The purpose of this study was to explore the impact of residents' experiences of fatigue and the strategies they use to manage it. Approach : This single-site study investigated the perceptions of resident physicians. Residents were recruited through purposive sampling to ensure representation from a variety of programs, postgraduate year level, and gender. Recruitment was managed with support from the residency programs; however, data collection and analysis were conducted by the Office of Postgraduate Medical Education to ensure participant anonymity. Program directors and administrators assisted in relaying the information about the study to the residents; however, they were not made aware if their residents participated in the study. Interview and focus group data were collected all at once, then transcribed, and then subsequent thematic analysis of these data was conducted using a quasi-constant comparison approach until thematic saturation was reached. Two researchers coded the data using thematic content analysis. Findings : Fifty-seven residents participated in a focus group or interview. There was representation from more than half of the 58 residency programs and from 15 of 16 departments. Overall, there was consensus that fatigue impacts residents' physical, cognitive, and emotional states. These impacts were reported as influencing resident performance including those related to patient care. Residents reported that fatigue led them to be less productive in their personal and professional lives. Three major themes were identified for which strategies could be developed for fatigue risk management: self, program, and system . Together with self-, program-, and system-level strategies that complement and enhance each other, specific targeted FRMPs could be developed. Insights : Fatigue is a multifaceted phenomenon experienced by residents that requires management beyond extended duty hours and adequate amounts of sleep. FRMPs that encompass strategies used by the resident, the residency-training program, and the healthcare system in which they work could assist with managing fatigue in residents and support enhanced resident well-being and patient care.